Influence of Information and Communication Technology on Secondary School Students' Academic Performance in Arabic Language - Taofeeq Olamilekan Sanusi (Naatiq: Journal of Arabic Education, 2025)
The study examined the influence of ICT on secondary school students' academic performance in the Arabic language in Kwara South of Nigeria. The study used a descriptive survey method with a population of 23,458 and 379 students from three Local Government Areas (LGAs) in Kwara South. The multistage sampling procedures involved purposive sampling to select three LGAs, stratified sampling to divide Kwara South into seven LGAs, and simple random sampling to select 30 public schools from each LGA. The Adapted Influence of ICT on Students' Performance Questionnaire (IICTAPQ) and Arabic Language Performance Test (ALPT) were used for data collection. The T-test method was adopted, and the data were analysed using Point-Biserial correlation statistics at a 0.05 significance level. The study found that audio-visual devices had a significant impact, but social media did not. The findings suggest that visual aids positively impact students' academic performance in Arabic, while social media does not. Therefore, visual aids are crucial for improving students' Arabic language skills. The study found that audio-visual devices positively impact secondary school students' academic performance in the Arabic language in Kwara South, Nigeria. However, social media negatively affects this performance. The study recommends using ICT-like visual devices, such as slides and projectors, to enhance students' interest and motivation in studying the language